Accurate quantification of bacterial abundance in metagenomic DNAs accounting for variable DNA integrity levels. Issue 10 (4th October 2020) - Manzari, Caterina; Oranger, Annarita; Fosso, Bruno; Piancone, Elisabetta; Pesole, Graziano; D'Erchia, Anna Maria
Abstract : The quantification of the total microbial content in metagenomic samples is critical for investigating the interplay between the microbiome and its host, as well as for assessing the accuracy and precision of the relative microbial composition which can be strongly biased in low microbial biomass samples. In the present study, we demonstrate that digital droplet PCR (ddPCR) can provide accurate quantification of the total copy number of the 16S rRNA gene, the gene usually exploited for assessing total bacterial abundance in metagenomic DNA samples. Notably, using DNA templates with different integrity levels, as measured by the DNA integrity number (DIN), we demonstrated that 16S rRNA copy number quantification is strongly affected by DNA quality and determined a precise correlation between quantification underestimation and DNA degradation levels. Therefore, we propose an input DNA mass correction, according to the observed DIN value, which could prevent inaccurate quantification of 16S copy number in degraded metagenomic DNAs. Our results highlight that a preliminary evaluation of the metagenomic DNA integrity should be considered before performing metagenomic analyses of different samples, both for the assessment of the reliability of observed differential abundances in different conditions and to obtain significant functional insights.